2021
DOI: 10.1093/hmg/ddab237
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptome-wide association study identifies novel susceptibility genes for psoriasis

Abstract: Although more than 80 psoriasis genetic risk loci have been reported through genome-wide association studies (GWASs), the genetic mechanism of psoriasis remains unclear. To identify novel candidate genes associated with psoriasis and reveal the potential effects of genetic factors in the development of psoriasis, we conducted a transcriptome-wide association study (TWAS) based on summary statistics from GWAS of psoriasis (5175 cases and 447 089 controls) and gene expression levels from six tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…We performed a tissue prioritization process using LDSC-SEG analysis using a multi-tissue RNA expression dataset and a multitissue chromatin modification dataset (Figure 2 and Supplementary Figure S1). Our tissue prioritization results led us to include additional relevant tissues (spleen, EBV-transformed lymphocytes, esophagus mucosa, and stomach) that were not used in the previous psoriasis TWAS study [63]. Previous studies have demonstrated that the spleen, lymphocytes, and gastrointestinal tract are associated with psoriasis [49,[64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…We performed a tissue prioritization process using LDSC-SEG analysis using a multi-tissue RNA expression dataset and a multitissue chromatin modification dataset (Figure 2 and Supplementary Figure S1). Our tissue prioritization results led us to include additional relevant tissues (spleen, EBV-transformed lymphocytes, esophagus mucosa, and stomach) that were not used in the previous psoriasis TWAS study [63]. Previous studies have demonstrated that the spleen, lymphocytes, and gastrointestinal tract are associated with psoriasis [49,[64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is a polygenic disease. More than 80 psoriasis risk loci have been reported (Zhu et al, 2021). Several of these genes are associated with the biological mechanisms as explained earlier.…”
Section: Psoriasis Susceptibility Genes Are Associated With Immune Me...mentioning
confidence: 90%
“…In this way, it is possible to determine the level to which all disease-associated variants within a locus contribute to differential gene expression, and is a powerful tool to relate risk genotype to function. Previous TWAS studies have uncovered novel putative psoriasis risk genes [35], with Jeong et al highlighting SSBP4 as significantly downregulated in psoriatic skin and fibroblasts [36]. SSBP4 increased transcription of interleukin 36 receptor agonist (IL36RA), IL-36RA reduces IL-36 activity, a cytokine has been found to stimulate IL-23 production and to have increased levels in psoriasis patients [37].…”
Section: Genes Associated With the Il-23 Pathwaymentioning
confidence: 99%